Analisis Pemberian Bakteri Probiotik Komersial pada Air Buangan Industri Tahu Terhadap Perubahan Kadar BOD dan DO dengan Interval Waktu Inkubasi 8 Jam - Justian Trisna Nugraha; Budi Utomo; Koosdaryani Soeryodarundio (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
This study aims to analyze the impact of administering commercial probiotic bacteria on the wastewater from tofu industries on changes in Bio-logical Oxygen Demand (BOD) and Dissolved Oxygen (DO) levels. Tofu industry wastewater is known to have high BOD and low DO levels, which pose a potential environmental pollution risk. This study used a pure experimental method with variables including the ratio of tofu industry wastewater to commercial probiotics (1:1, 1:2, 1:3) with an incubation interval of 8 hours. The results showed that the administration of commercial probiotic bacteria significantly reduced BOD levels and increased DO levels in the wastewater. The 1:3 ratio of tofu industry wastewater to commercial probiotics showed the most optimal effect in increasing DO and decreasing BOD. An incubation time of 32 hours showed the most optimal effect in increasing DO and decreasing BOD. The 1:3 volume ratio between tofu wastewater and probiotics (25% tofu wastewater and 75% probiotics) proved to be the most effective, with the highest DO increase of 2.51 mg/L and the largest BOD decrease of 144.20 mg/L. In addition, incubation time also had a significant effect, the longer the incubation time, the more optimal the probiotic activity in reducing BOD levels and increasing DO levels. The conclusion of this study is that the administration of commercial probiotic bacteria at a 1:3 ratio and an incubation time of 32 hours is an effective way to improve the quality of tofu industry wastewater.